The Foundation Of A Sakinah Family: Family Counseling - Cristy Winata (Journal of Therapia, 2024)
The article discusses important principles in building a harmonious marriage and family relationship from an Islamic perspective. The process of selecting a life partner, marriage in Islam, solutions to marriage challenges, and marriage procedures are the main focus of the discussion. In conclusion, it is important for individuals to pay attention to criteria and preferences in choosing a partner, with religious factors being the top priority. Marriage is seen as human nature that involves physical, spiritual, and human values. In facing the challenges of marriage, it is important to learn more about one's partner, appreciate each other, and recall important moments in the relationship. Emotional, physical, and mental maturity as well as the principles of Islamic family guidance and counseling are also important in marriage procedures. In addition, the article also emphasizes the importance of patience and tawakakal, the utilization of Islamic principles in solving problems, the consideration of factors such as wealth, descent, beauty, and religion in the selection of a partner, as well as self-adjustment, social support, and understanding of developmental tasks during pregnancy to create a happy and thriving family life. By understanding and applying these principles, individuals are expected to build harmonious marriage and family relationships in accordance with religious teachings and human values.